The nuclear factor E2-related factor 2 and age-related macular degeneration - Torres, Rogil José De Almeida [UNESP]; Torres, Rogério João De Almeida; Luchini, Andréa; Ferreira, Ana Lúcia Dos Anjos [UNESP] (Conselho Brasileiro de Oftalmologia, 2022)
After the discovery of anti-vascular endothelial growth factor agents as treatment of wet age-related macular degeneration, the number of studies with the objective to understand the molecular mechanisms involved in the age-re lated macular degeneration genesis has increased. The importance of the nuclear factor e2-related factor 2 lies in its activation-derived proteins being involved in the maintenance of the redox balance and consequent prevention of degenerative macular disease. This article aims to present the characteristics of nuclear factor e2-related factor 2 and describe the main nuclear factor e2-related factor 2-activated antioxidant enzymes that contribute to the preservation of vision.

Após a descoberta do anti fator de crescimento en dotelial vascular no tratamento da degeneração macular relacionada à idade úmida, muitas pesquisas têm sido realizadas com o intuito de elucidar os mecanismos moleculares envolvidos na gênese da degeneração macular relacionada à idade. O fator nuclear eritroide 2 relacionado ao fator 2 destaca-se pelo fato de diversas proteínas, oriundas de sua ativação, estarem envolvidas na manutenção do equilíbrio do estado redox e consequente prevenção da doença macular degenerativa. Este artigo mostra as características do fator nuclear eritroide 2 relacionado ao fator 2 e descreve as principais enzimas antioxidantes originadas da ativação que contribuem para a preservação da visão.
O fator 2 relacionado a NF-E2 e a degeneração macular relacionada à idade
Keywords: Macular degeneration; NF-E2-Related Factor 2; Oxidation; Antioxidant response element; Enzyme activator; Degeneração macular; Fator nuclear eritroide 2 relacionado ao fator 2; Oxidação; Elemento de resposta antioxidante; Ativador de enzima